2021
DOI: 10.3389/fphys.2021.699142
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Thermal Manipulation Affects Ventilation, Metabolism, Thermal Control and Central Dopamine in Newly Hatched and Juvenile Chicks

Abstract: The first third of incubation is critical for embryonic development, and environmental changes during this phase can affect the physiology and survival of the embryos. We evaluated the effects of low (LT), control (CT), and high (HT) temperatures during the first 5 days of incubation on ventilation (V.E), body temperature (Tb), oxygen consumption (V.O2), respiratory equivalent (V.E/V.O2), and brain monoamines on 3-days-old (3d) and 14-days-old (14d) male and female chickens. The body mass of LT animals of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 81 publications
1
9
0
Order By: Relevance
“…Short-term (intermittent) alteration in incubation temperature during varying age of embryogenesis can boost muscle growth and development at hatch and in the first weeks post-hatch (early period (E0-E5) [22]; mid-term (E16-E18) [59]; long-term (E12-E18 and E10-E21) [60]). In the current review, the similar effect was identified with short and long-term TM (36.8°C for 24 h/d from E7 to E13 [32]; 39°C for 9-18 h/d from E10 to E18 [37,50]; 36.°C for 6 h/d from E10 to E5 [2]), which was indicated by increased embryo, hatch and 1-day-old chick weight. In addition, it is evidenced that TM has significant effect on proliferation and differentiation of satellite cells, and thus growth and development of embryonic and chick muscles [61].…”
Section: Thermal Manipulation and Embryo Hatch Or Chick Weightsupporting
confidence: 74%
See 4 more Smart Citations
“…Short-term (intermittent) alteration in incubation temperature during varying age of embryogenesis can boost muscle growth and development at hatch and in the first weeks post-hatch (early period (E0-E5) [22]; mid-term (E16-E18) [59]; long-term (E12-E18 and E10-E21) [60]). In the current review, the similar effect was identified with short and long-term TM (36.8°C for 24 h/d from E7 to E13 [32]; 39°C for 9-18 h/d from E10 to E18 [37,50]; 36.°C for 6 h/d from E10 to E5 [2]), which was indicated by increased embryo, hatch and 1-day-old chick weight. In addition, it is evidenced that TM has significant effect on proliferation and differentiation of satellite cells, and thus growth and development of embryonic and chick muscles [61].…”
Section: Thermal Manipulation and Embryo Hatch Or Chick Weightsupporting
confidence: 74%
“…Among the 24 intermittent TM studies, 20 articles reported the TM effect on hatchability, of which 65% found no significant effect, 30% being reduced, and a comparative study by Dalab and Ali [46] reported increased and decreased hatchability at different embryonic age. Meanwhile, embryo and/or hatch weight and chick quality were reported in 18 articles, of which 12 (67%) found no significant effect, three studies reported increased [2,38,50], and three reported reduced effect of TM on embryo and/or hatch weight and chick quality [42,45,46].…”
Section: Search Strategy and Selection Of Publicationsmentioning
confidence: 99%
See 3 more Smart Citations